Late adolescence community understanding Towards Halal Food - Fitri Rafianti; Emi Wakhyuni; Muhammad Andafi (Yayasan Multidimensi Kreatif, 2024)
Adolescents (late adolescence) experience developments that often result in a seemingly uncertain position, therefore society is difficult to determine norms for adolescents because their status is between children and adults. As a result, it is difficult for adolescents to determine their attitude so that this often causes turmoil within the teenager, which greatly affects their will and the food they consume. Physical and spiritual health is needed to balance the lifestyle of adolescents, where we see today's teenagers pay less attention to a healthy lifestyle and halal technological developments certainly greatly affect the choices made by adolescents. The problem in this study is how late adolescence understands halal food then the method used in this research is normative legal research where normative legal research takes data with a statutory approach and other legal sources. The results of this study indicate that many adolescents do not know the boundaries of halal and haram food so it is very important to provide a very basic understanding up to the regulatory stage, introduction to halal certification, halal certification policy criteria and halal and thoyyib principles in food products. Teenagers as the next generation of the nation need to know this because food is something that is consumed will grow into the flesh and blood and behavior and even actions of a teenager.